2015
DOI: 10.1021/jacs.5b03629
|View full text |Cite
|
Sign up to set email alerts
|

A Semisynthetic Strategy Leads to Alteration of the Backbone Amidate Ligand in the NiSOD Active Site

Abstract: Computational investigations have implicated the amidate ligand in nickel superoxide dismutase (NiSOD) in stabilizing Ni-centered redox catalysis and in preventing cysteine thiolate ligand oxidation. To test these predictions, we have used an experimental approach utilizing a semisynthetic scheme that employs native chemical ligation of a pentapeptide (HCDLP) to recombinant S. coelicolor NiSOD lacking these N-terminal residues, NΔ5-NiSOD. Wild-type enzyme produced in this manner exhibits the characteristic spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 74 publications
1
15
0
Order By: Relevance
“…32, 33 This model simulates the formation of five-membered chelate rings that form when the binding of the N-terminal amine is accompanied by backbone amide binding, which lead to the ordering of second coordination sphere C atoms similar to prior models of backbone amidate ligation in the active site of NiSOD. 34, 35 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…32, 33 This model simulates the formation of five-membered chelate rings that form when the binding of the N-terminal amine is accompanied by backbone amide binding, which lead to the ordering of second coordination sphere C atoms similar to prior models of backbone amidate ligation in the active site of NiSOD. 34, 35 …”
Section: Resultsmentioning
confidence: 99%
“…4648 Both the E. coli HypB N-terminal motif and NiSOD Ni binding sites have been referred to as “ATCUN-like” in literature due to the binding of the N-terminal amine and planar geometry. 35, 45, 46 Another example of Ni-binding at the N-terminus can be found in E. coli RcnR, a Ni(II)-/Co(II)-responsive transcriptional regulator, which binds Ni(II) with the N-terminal amine of Ser2 (Met1 is cleaved in E. coli ) in a 6-coordinate site, where there is no evidence of backbone amide binding thus far. 49 Thus, Ni(II) binding at the N-terminal amine has been found in proteins with vastly different functions and metal coordination: metal transporters/chaperones ( e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Photochemical deprotection of oNB could then be achieved by irradiation at 365 nm (100 mM NaOAc, 20 mM TCEP, 10 mM semicarbazide, pH 5.8). 244 Cys(oNB) can also be incorporated into proteins via unnatural amino acid mutagenesis 245,246 as demonstrated with a photocaged human superoxide dismutase (nbC-33-hSOD, Fig. 31b), 246 along with being used to study protein activity, 247,248 As discussed previously, Cys(oNB) is also orthogonal to Pd-mediated deprotection of Acm, as recently displayed in the synthesis of Linaclotide and plectasin (Fig.…”
Section: Benzyloxymethyl (Bom)mentioning
confidence: 86%
“… 19 and work cited therein), peptide-based NiSOD maquettes were assumed to be stable against oxygen 20 and predicted to be unstable against H 2 O 2 on the basis of theoretical calculations 21 . In a more recent study a bis-amidate NiSOD model peptide was found to show rapid ligand-based sulfur oxidation which was thought to cause its inactivity while no such oxidation was observed for the native-like amine/amide metallopeptide 20 , 22 , 23 . This is rather surprising since the same native-like amine/amide NiSOD mimic was observed to degrade rapidly on air in an early study from the same author 24 .…”
Section: Introductionmentioning
confidence: 99%